The negative impact of attention distractors on the progress of the learning process from the perspective of a sample of primary school teachers in Laghouat Province - Atallah, Benyahia; Abdelbasset, Gouni (International journal of health sciences, 2024)
The study aimed to identify the impact of attention distractors on the classroom learning process from the perspective of a sample of primary school teachers in Laghouat Province. The descriptive exploratory method was used to align with the study's objectives. Furthermore, a questionnaire was developed regarding auditory and visual attentional distractors. The study concluded that the negative impact of attention distractors on the classroom learning process was significant, according to the opinions of the study sample.